Development of Word Board Learning Media to Overcome Reading Difficulties of Third Grade Elementary School Students - Fathya Andini; Sapri Sapri (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah)
Third-graders at SDN 064961 Kampung Baru, Kec. Medan Maimun has a low interest in reading, which results in poor reading skills. Therefore, researchers developed word board media to overcome students' reading difficulties. The advantage of this word board media is that it contains letter recognition filled with colours, the letters displayed by the researcher have been adjusted to the needs of students, and the media also focuses on the nuances of the images so that students can easily understand and improve memory. This study aims to develop practical and effective word board learning media for overcoming reading difficulties for grade III students at SDN 064961 Kampung Baru, Kec. Medan Maimun. This research uses the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The results of the study revealed that 1) word board media is very feasible to use with Aiken's V result in media experts of 0.95; 2) the word board media is efficient to use; this is proven by the V Aiken value in the student response which is 0.994 and the V Aiken value in the teacher's response of 0.95; 3) through the t-paired test the score and score are obtained; and the average N-Gain score is 0.7; the word board media is very effective in helping to overcome reading comprehension difficulties in grade III elementary school students.